2022
DOI: 10.1002/advs.202201212
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Omics‐Based Autophagy‐Related Untypical Subtypes in Patients with Cerebral Amyloid Pathology

Abstract: Recent multi-omics analyses paved the way for a comprehensive understanding of pathological processes. However, only few studies have explored Alzheimer's disease (AD) despite the possibility of biological subtypes within these patients. For this study, unsupervised classification of four datasets (genetics, miRNA transcriptomics, proteomics, and blood-based biomarkers) using Multi-Omics Factor Analysis+ (MOFA+), along with systems-biological approaches following various downstream analyses are performed. New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Human pluripotent stem cell (hPSC) models have offered an avenue to study microglial function in AD in a human living system. AD patient‐derived microglia have been utilized for study in mono‐cultures (Cosker et al, 2021; Konttinen et al, 2019; Monzón‐Sandoval et al, 2022; Piers et al, 2020; Wißfeld et al, 2021; Xu et al, 2019), tri‐cultures with astrocytes and neurons (Bassil et al, 2021; Grubman et al, 2020; Guttikonda et al, 2021; Park et al, 2018; Reich et al, 2021) and 3D cultures with organoids (Brownjohn et al, 2018; Cakir et al, 2022; Lin et al, 2018; Park et al, 2022). The use of 2D and 3D co‐cultures and organoids allows for increased ramification and motility and the expression of disease‐associated genes, which better resemble native microglia, compared to mono‐cultures (Grubman et al, 2020; Haenseler et al, 2017; Popova et al, 2021; Reich et al, 2021).…”
Section: New Insights From Stem Cell‐derived Microglia and Their Tran...mentioning
confidence: 99%
See 1 more Smart Citation
“…Human pluripotent stem cell (hPSC) models have offered an avenue to study microglial function in AD in a human living system. AD patient‐derived microglia have been utilized for study in mono‐cultures (Cosker et al, 2021; Konttinen et al, 2019; Monzón‐Sandoval et al, 2022; Piers et al, 2020; Wißfeld et al, 2021; Xu et al, 2019), tri‐cultures with astrocytes and neurons (Bassil et al, 2021; Grubman et al, 2020; Guttikonda et al, 2021; Park et al, 2018; Reich et al, 2021) and 3D cultures with organoids (Brownjohn et al, 2018; Cakir et al, 2022; Lin et al, 2018; Park et al, 2022). The use of 2D and 3D co‐cultures and organoids allows for increased ramification and motility and the expression of disease‐associated genes, which better resemble native microglia, compared to mono‐cultures (Grubman et al, 2020; Haenseler et al, 2017; Popova et al, 2021; Reich et al, 2021).…”
Section: New Insights From Stem Cell‐derived Microglia and Their Tran...mentioning
confidence: 99%
“…Human pluripotent stem cell (hPSC) models have offered an avenue to study microglial function in AD in a human living system, in 2D mono‐cultures (Cosker et al, 2021; Konttinen et al, 2019; Monzón‐Sandoval et al, 2022; Piers et al, 2020; Wißfeld et al, 2021; Xu et al, 2019), co‐cultures (Bassil et al, 2021; Grubman et al, 2020; Guttikonda et al, 2021; Park et al, 2018; Reich et al, 2021) or in 3D, within brain organoids (Brownjohn et al, 2018; Cakir et al, 2022; Lin et al, 2018; Park et al, 2022). To conserve age‐associated factors, the transdifferentiation of peripheral blood mononuclear cells (PBMCs) or monocytes from patients can be used to rapidly generate microglia within 2 weeks (Banerjee et al, 2021; Quek, Cuní‐López, Stewart, Lim, et al, 2022; Ryan et al, 2017; as reviewed by Sargeant & Fourrier, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Induced pluripotent stem cell (iPSC)-derived microglial cell culture, IgG treatment, and imaging iPSC-derived microglia were generated according to the protocol described in our previous study (Park et al, 2022). Monomeric Ab 1-42 (1 mM; Bachem Holding, Bubendorf, Switzerland) was used for 4 days to mimic mild Ab (acute model) conditions.…”
Section: Author Contributionsmentioning
confidence: 99%
“…On the other hand, blood (or systemic)-derived multi-omics data are better suited to identify biomarkers for individual diagnosis, prognosis and monitoring. For example, using readily accessible blood-derived genomics, transcriptomics and proteomics data from patients with cerebral amyloid pathology, Park et al (2022) have identified possible molecular drivers of AD heterogeneity or AD subtypes. This suggests that specific clinical manifestations of AD could be associated with distinct biological alterations.…”
Section: The Promise Of Personalised Medicinementioning
confidence: 99%